2011
DOI: 10.1080/10298436.2011.575138
|View full text |Cite
|
Sign up to set email alerts
|

Cohesive zone model to predict fracture in bituminous materials and asphaltic pavements: state-of-the-art review

Abstract: Cohesive zone (CZ) modeling has been receiving increasing attention from the asphaltic materials and pavement mechanics community as a mechanistic approach to model crack initiation and propagation in materials and structures. The CZ model provides a powerful and efficient tool that can be easily implemented in existing computational methods for brittle, quasi-brittle, and ductile failure as well as interfacial fracture, all of which are frequently observed in asphaltic materials. Accordingly, this paper intro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(8 citation statements)
references
References 111 publications
(100 reference statements)
0
7
0
Order By: Relevance
“…CZM has been employed to simulate crack propagation in asphalt mixes with indirect tension (ID(T)) test (Soares et al 2003), semi-circular bend (SCB) Marasteanu 2005, 2009), three-point bend (SE(B)) or mixed-mode SE(B) (Song et al 2006a(Song et al , 2006b, double edge notchedbar (Tijssens et al 2000) and DC(T) (Wagoner et al 2005a, Song et al 2008) test configurations. An extensive literature review on fracture simulation of bituminous materials using the CZM approach is found in a recent publication of Kim (2011).…”
Section: Fe Modelling Of Fracture Of Asphalt MIX Beamsmentioning
confidence: 99%
“…CZM has been employed to simulate crack propagation in asphalt mixes with indirect tension (ID(T)) test (Soares et al 2003), semi-circular bend (SCB) Marasteanu 2005, 2009), three-point bend (SE(B)) or mixed-mode SE(B) (Song et al 2006a(Song et al , 2006b, double edge notchedbar (Tijssens et al 2000) and DC(T) (Wagoner et al 2005a, Song et al 2008) test configurations. An extensive literature review on fracture simulation of bituminous materials using the CZM approach is found in a recent publication of Kim (2011).…”
Section: Fe Modelling Of Fracture Of Asphalt MIX Beamsmentioning
confidence: 99%
“…Kim & Aragao, 2013; Y.‐R. Kim et al., 2007; Rodrigues et al., 2019) that are limited in their capacity to fully account for the rate‐dependent cracking of bituminous materials.…”
Section: Model Application and Validationmentioning
confidence: 99%
“…Kim & Aragao, 2013; H. Kim & Buttlar, 2009; Y.‐R. Kim et al., 2007; Soares et al., 2003) have demonstrated the ability of CZMs to predict fracture and damage behavior of bituminous materials, mixtures, and pavements. Considering that bituminous media exhibit highly rate‐dependent viscoelastic and nonlinear behavior, cracking can be effectively modeled by the extrinsic nonlinear viscoelastic cohesive zone (NVCZ).…”
Section: Introductionmentioning
confidence: 99%
“…Pertillo and Cebon (2013) conducted a numerical and experimental evaluation of the mechanism of bitumen beams cracking. The researchers performed their experiments on bitumen rather than on the mixture to run the microstructural studies on the pure bitumen fracture (Kim, Y. K., 2011). The fracture parameters used in this study were K IC , G IC , and J integral, which were used to evaluate fracture properties by three-point bending experiment on pure bitumen beams.…”
Section: Introduce the Problemmentioning
confidence: 99%